Smooth model of blasting seismic wave signal denoising based on two-stage denoising algorithm. Issue 4 (3rd July 2020) - Sun, Miao; Wu, Li; Li, Chunjun; Yuan, Qing; Zhou, Yuchun; Ouyang, Xu
ABSTRACT: In this paper, a two-stage denoising algorithm is proposed. Complementary ensemble empirical mode decomposition based on permutation entropy (CEEMD-PE) is carried out for the noisy monitoring signal in the first stage. Several denoising models are established according to the intrinsic mode function obtained by CEEMD-PE. An objective function considers both the smoothness of the denoising model and the similarity between the denoising model and the noisy monitoring signal is established, and the second stage denoising is realized by solving the objective function. The denoising model corresponding to the optimal solution of the objective function is the smooth denoising model. In order to verify the correctness of the two-stage denoising algorithm, the mixed simulation signal with noise is denoised, and based on the definition of signal-to-noise ratio, the effect of two-stage denoising is calculated. Finally, the algorithm is applied to the actual blasting seismic signal denoising processing. It is found that the proposed algorithm can not only reduce the noise interference but also retain the real part of the original signal while filtering the noise.